Utilization of quaternary solvent mixtures for extraction of lipids from Scenedesmus obliquus microalgae. Issue 1 (1st January 2020) - Mustapha, Sherif Ishola; Isa, Yusuf Makarfi
Abstract: Solvent toxicity is of major concern in the extraction of lipid from algae biomass via the solvent extraction technique. This study was carried out to determine the optimal solvent mixture (chloroform, methanol, ethanol, and dichloromethane) composition with less toxicity for the extraction of lipids from Scenedesmus obliquus microalgae. Optimization of the solvent mixture composition was performed using augmented simplex centroid design and the influence of cell disruption on lipid yield was assessed. The eco-toxicity of the solvent mixtures was assessed using thermodynamic prediction model. The optimal lipid yield of 19.4% lipid g-1 DCW (dry cell weight) was obtained using solvent mixture composition (1:5:1:1 v/v) chloroform/methanol/ethanol/dichloromethane. The cost estimation and environmental risk parameter values obtained from the use of proposed quaternary solvent mixture composition indicated that lower cost and less toxicity were achieved when compared with the commonly used chloroform-methanol mixture composition. Microwave-assisted lipid extraction gave 55.67% higher lipid recovery from microalgae and the quality of the extracted lipid was unaffected when compared with the conventional solvent extraction. The fatty acid profile revealed the extracted lipids as an appropriate feedstock for biodiesel production. Applicability of lipid extracted biomass obtained using the proposed technique is confirmed by SEM and FTIR analyses.